The Extent of Information Technology (IT) Use in Accounting: A Case of Sarawak - Goi, Chai; Ho, Poh-Ling; Choo, Samuel; Yong, S. (Global Academy of Business and Economic Research, 2008)
The main objective of this study is to examine the extent of IT used in accounting based on Sarawak state. This study found that even majority of the respondents' claimed that they have adopted of computer-based accounting system for more than 9 years, but adoption of fully computerised or fully computerised link to web applications still very low. The results indicate that the most popular method of implementing the accounting software is by utilising the ready-made packages and uses batches system to process their data. The average use of different accounting modules with the general ledger recorded the highest. The subsidiary ledgers, which include sales/Accounts Receivable, purchases/Accounts Payable, payroll and inventory management and control, are also frequently used by the sample firms. However, other computerised support functions are not commonly employed. The three highest reported problems in adopting computer-based accounting system are inadequate skills or expertise, limited functions of the accounting software, and poor vendor support. Finally, due to low adoption of fully computerised or fully computerised link to web applications, the correlation between the extent of IT used with the age of companies, location, number of employees and industry are not strong.